Genetic architecture of the maize kernel row number revealed by combining QTL mapping using a high-density genetic map and bulked segregant RNA sequencing. (December 2016) - Liu, Changlin; Zhou, Qiang; Dong, Le; Wang, Hui; Liu, Fang; Weng, Jianfeng; Li, Xinhai; Xie, Chuanxiao
Abstract Background The maize kernel row number (KRN) is a key component that contributes to grain yield and has high broad-sense heritability (H 2 ). Quantitative trait locus/loci (QTL) mapping using a high-density genetic map is a powerful approach to detecting loci that are responsible for traits of interest. Bulked segregant ribonucleic acid (RNA) sequencing (BSR-seq) is another rapid and cost-effective strategy to identify QTL. Combining QTL mapping using a high-density genetic map and BSR-seq may dissect comprehensively the genetic architecture underlying the maize KRN. Results A panel of 300 F2 individuals derived from inbred lines abe2 and B73 were genotyped using the specific-locus amplified fragment sequencing (SLAF-seq) method. A total of 4, 579 high-quality polymorphic SLAF markers were obtained and used to construct a high-density genetic map with a total length of 2, 123 centimorgan (cM) and an average distance between adjacent markers of 0.46 cM. Combining the genetic map and KRN of F2 individuals, four QTL (qKRN1, qKRN2, qKRN5, andqKRN8-1 ) were identified on chromosomes 1, 2, 5, and 8, respectively. The physical intervals of these four QTL ranged from 4.36 Mb forqKRN8-1 to 7.11 Mb forqKRN1 with an average value of 6.08 Mb. Based on high-throughput sequencing of two RNA pools bulked from leaves of plants with extremely high and low KRNs, two QTL were detected on chromosome 8 in the 10–25 Mb (BSR_QTL1 ) and 60–150 Mb (BSR_QTL2 ) intervals. According to the physical positions of these QTL, qKRN8-1 was included byBSR_QTL2 . In addition, qKRN8-1 was validated using QTL mapping with a recombinant inbred lines population that was derived from inbred lines abe2 and B73. Conclusions In this study, we proved that combining QTL mapping using a high-density genetic map and BSR-seq is a powerful and cost-effective approach to comprehensively revealing genetic architecture underlying traits of interest. The QTL for the KRN detected in this study, especiallyqKRN8-1, can be used for performing fine mapping experiments and marker-assisted selection in maize breeding.